Development of a panorama coded-aperture gamma camera for radiation detection. (June 2015) - Sun, Shifeng; Zhang, Zhiming; Shuai, Lei; Li, Daowu; Wang, Yingjie; Liu, Yantao; Huang, Xianchao; Tang, Haohui; Li, Ting; Chai, Pei; Jiang, Xiaopan; Ma, Bo; et al.
Abstract: For radiation detection, the imaging system should have a large field of view (FOV) and high detection efficiency because it has to be used in a radiation environment where the quantity and direction of radioactive sources are unknown. A panorama coded-aperture gamma camera optimized for use in complex nuclear environment has been developed and evaluated with an angular resolution of 3.5°. Typical gamma cameras have the limited field of view ranging from 10° to 60° in both horizontal and vertical direction. The system presented in this paper extends the field of view to 360° in the horizontal direction and 60° in the vertical direction. The partial encoding of coded aperture imaging is mitigated by convolving the data of diverse adjacent modules with a partial transmission function. The experimental feasibility of measuring multiple sources in the 360° horizontal field of view was demonstrated with a panoramic image. The results showed that the system could clearly identify the direction of multiple radiation sources in an unknown extended radiation environment. The system can help to simplify the clean up and decommissioning of nuclear sites. Highlights: Development of a coded-aperture gamma camera. Panoramic gamma ray imaging in real time. Mitigate the partial encoding of coded aperture imaging (CAI). Experimental validation.